Active biocomposite packaging films: Compatibility of carrageenan with cellulose nanofiber from empty fruit bunches - Nurul Aini, Mohd Azman (Elsevier, 2022)
Biodegradable films are used for protection and to extend the shelf life of food products. A biodegradable film could be defined as a packaging made from biodegradable polymers and food grade additives. Biopolymers such as lipids, proteins, polysaccharides, and mixtures have been investigated to enhance the properties of films as packaging materials. Seaweeds are one of polysaccharides compounds belong to the simplest group of plants, known as algae. Commonly, seaweeds will undergo extraction process to produce refined carrageenan or semirefined carrageenan. Cellulose constitutes the most abundant renewable polymer resource available in nature and has been widely reported as a raw material for biodegradable films due to its renewability, low cost, nontoxicity, biocompatibility, biodegradability, and chemical stability. Plant cellulose can improve the mechanical and barrier properties of seaweed films due to the chemical similarity of seaweed and cellulose, making them highly compatible. Plasticizers are added to provide the necessary workability to biopolymers. Glycerol is a highly hygroscopic molecule generally incorporated in most hydrocolloid films to allow the modification of the functional properties of films by increasing their flexibility, extensibility, elasticity, and mechanical properties. Incorporation of antioxidants into packaging materials has become popular since oxidation is a major problem affecting food quality. There has been increasing interest in the role of tocopherol (vitamin E) used as a food additive due to its effective inhibition of lipid oxidation in foods. α-tocopherol exhibits excellent antioxidant potency at optimum concentrations and is widely used as an antioxidant added directly to food or in the production of packaging materials.